Erase The Disciplinary Penalty as A Guarantee For Employees to Remove its Effects - Kadhim, Sarmad Jawad (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a comparative analysis of the erasure of disciplinary penalties for public employees in the context of organizational and statutory relationships with the state. The study explores the historical evolution of terminology used in Iraqi legislation, transitioning from